(untitled) (Research, Society and Development, 2021)
The objective of this work was to carry out a systematic review of the scientific production on the use of species distribution modeling for forest restoration. Searches for scientific articles in the Scopus and Web of Science databases for the last 15 years were performed in December 2020 using the terms: "ecological modeling" OR "biodiversity modeling" OR "predictive models" OR "modeling of niche" OR "habitat models" AND "species distribution" OR "geographic distribution" OR "potential distribution" AND "forest restoration" OR "restoration ecology". For the statistical and graphical analysis of the raw data the Bibliometrix package was used of the R software. The raw data were refined by selecting the studies that meet the following criteria: (i) studies published in scientific journals with an impact factor equal to or greater than 2.0; (ii) studies in which the title or abstract mentioned as words forest restoration or ecological restoration; (iii) studies that evaluate the use of species distribution modeling as an aid to forest restoration or restoration projects and programs the ecological. found 44 documents published in 30 scientific journals with an average of 3.91 publications per year; 18.55 citations per document; 197 authors, 3 documents with single authorship. Thus, we were able to conclude that the use of species distribution modeling for forest restoration in the world is very recent, and in Brazil it is incipient with low numbers of published articles. Still, it shows a growing trend due to its significant contribution to improving success rates restoration projects.